Faktor Relationship Benefits yang Meningkatkan Positive Word of Mouth di Toko Buku Impor X - Petrus Hepi Witono; Frederikus Fios; Renny Risqiani (Jurnal Syntax Admiration, 2024)
This study aims to analyze the effect of relationship benefits on the creation of positive Word of Mouth (WOM) in imported bookstore X. In the context of increasingly competitive marketing, Word of Mouth has become a strategic focus for companies as an effective and economical alternative in influencing consumer behavior. The research method used Purposive Sampling with 200 respondents aged 18-45 years who had shopped at imported bookstore X. The majority of respondents were women (59.5%), aged 25-34 years (39.5%), and S1 graduates (56.5%). The analysis is carried out using the Structural Equation Modeling (SEM) method to examine the relationship between variables. The study involved 9 variables, including trust benefits, special treatment benefits, social benefits, information benefits, sharing benefits, functional quality, technical quality, relationship quality, and word of mouth. The results of the analysis show that Confidence Benefit and Sharing Benefit have a significant influence in increasing the sense of security and desire to share from store employees. Relationship Quality is also important to increase customer trust and satisfaction. Word of Mouth becomes a major factor in improving sales perception and reputation. This research provides a deep understanding of the role of Relationship Benefits in creating positive Word of Mouth in the retail environment, providing strategic implications for companies in designing effective WOM-based marketing programs to influence consumer preferences.